P14.93 Partial stiff-person syndrome, cerebral lymphoma, and HIV infection. (9th September 2021) - Ivan, R; Cîrciumaru, B; Poșircă, C M; Sîrbu, C A
Abstract: BACKGROUND: Stiff person syndrome (SPS) is a rare entity, characterized by rigidity or stiffness of the muscles. It is usually autoimmune, but it can also appear as a paraneoplastic (5%) or cryptogenic disorder. This study aims to establish a potential connection between what appears to be a partial SPS, an advanced HIV infection, and a primary central nervous system (CNS) lymphoma in a young adult. MATERIAL AND METHODS: We present the case of a 42-year-old male, who, in the course of approximately five months developed dizziness, impairment of manual dexterity, ataxia, postural instability, hallucinations, weight loss, and fever. He was admitted to our clinic, after a progressive deterioration of his mental status, presenting global aphasia, and increased left hemibody muscle tone, with persistent left torticollis. According to the blood tests and cerebral MRIs he was diagnosed with HIV infection, thrombophilia, and a left frontal mass, of unknown etiology. RESULTS: His neurocognitive deterioration was suggestive of a primary CNS lymphoma and the ipsilateral abnormal increased muscular tone raised the suspicion of a partial SPS. It appeared most likely in the context of the brain lesion, even if its nature remained unknown, due to the deteriorated status, that made biopsy impossible. The diagnosis of cerebral lymphoma was based on the IRM characteristics and the change in appearance after corticosteroid therapy. CONCLUSION: Even if it represents a rare diagnosis, partial SPS can appear as a paraneoplastic entity, our patient's evolution and clinical examination being suggestive for this pathology.